Sistem Rantai Pasok Pupuk Area - Harry Rahmadi Putra; Fandra Nanda; Yusra Hadi; Agus Wibowo; Dio Putera Hasian (Jurnal Optimasi Sistem Industri, 2011)
PT. Pupuk Kaltim is biggest manure manufacturer in Indonesia, where its market area covering entire Sulawesi, Bali, some of Kalimantan East Java, Papua, Japan, Taiwan, India, and Australia. Main produced product of PT Pupuk Kaltim is based fertilizer. To meet the demand, PT Kaltim produce up to 2,3 million tons per year.Identifiaction process of supply chain done by accesing company website of PT Kaltim. Then it is outlined each step of supply chain from aggregate planning, production process, suppliers selection, quality mangement, warehousing, performance measure and used transportation unit. From that criteria would visible supply chain of based-fertilizer in PT Pupuk Kaltim. By having long and wide supply chain, PT Pupuk Kaltim still have bullwhip effect because of inacurate in forecasting cause over-stock or out of stock in many production period. In quality, PT Kaltim had got ISO 9001, ISO 14001 and ISO 17025 certification in production management and sea-port.